Gerakan Sosial: Perlawanan Petani Puger Terhadap PT Semen Imasco Asiatic (Jurnal ENTITAS SOSIOLOGI, 2023)
The resistance of the Puger peasants is part of the representation of class oppression. The social conflict that befell the lower class, in this case the Puger peasants, is in fact a form of domination of power which can be seen from PT Imasco Asiatic's unilateral attitude in changing the irrigation channel. This is because the channel is the main source for irrigating the rice fields of Puger Wetan and Puger Kulon villages. According to the research results, the conflict between Puger farmers and PT Imasco Asiatic can be categorized as a form of resistance that leads to social movements. As a result, the farmers suffered losses due to the relocation of the irrigation channel. So, together with PMII Jember, the farmers took action to express their aspirations. Thus, the farmers hope that from this action they will be able to find the best solution and the conflict that befell them will end soon. This writing tends to apply qualitative methods with a descriptive analysis approach. This study also used non-participant observation techniques and literature study in collecting data. Then, after the data has been collected, the data is analyzed using several theories, such as the theory of resistance (resistance) and social movements. In this way, researchers can easily categorize the types, forms, and stages of each data.